ANALISIS KEMAMPUAN METAKOGNISI PADA SISWA SMPN 23 PEKANBARU KELAS VIII PADA PEMBELAJARAN IPA BIOLOGI TAHUN AJARAN 2014/2015 - Mariani Natalina L; Yustini Yusuf; Nurdina " (Biogenesis, 2015)
ABSTRACT The aim of this research is to analyze student's metacognition skill profiles atSMPN 23 Pekanbaru academic year 2014/2015. This research was performed on 17th to 28th November 2014. The sample in this research is class VIII as many as 108 students were selected through stratified sampling technique. The data collection instruments used were a closed questionnaire and interview. The whole point questionnaire covered otherwise valid and reliable. The collected data were analyzed descriptive. Picture of student’s metacognition skills of SMPN 23 Pekanbaru obtained as follows: metacognition abilities of students in designing learning strategies (Planning) has developed differently with a score of metacognition 73, metacognition skills of students in selecting and using learning strategies ( Management Strategies) developed very well expressed by a score of metacognition 81, the ability to monitor student’s metacognition learning strategies (Monitoring) has developed differently with a score of metacognition 73, student’s metacognition skills in combining different learning strategies (Debugging) expressed always very good with metacognition score of 81 in the assessment of the ability of metacognition learning strategies student’s (Evaluation) declared progressing well with a score of 79. Overall, the metacognition scores of students is 77, then student’s metacognition skill profiles of SMPN 23 Pekanbaru class VIII in Biology Science Education declared the school year 2014/2015 is growing very well. Key words: profile of student metacognition skill, junior high school, sainsBiology learning